Cyclophosphamide treatment-induced leukopenia rates in ANCA-associated vasculitis are influenced by variant CYP450 2C9 genotypes. (March 2016) - Schirmer, Jan Henrik; Bremer, Jan Phillip; Moosig, Frank; Holle, Julia Ulrike; Lamprecht, Peter; Wieczorek, Stefan; Haenisch, Sierk; Cascorbi, Ingolf
Aim: Correlation of outcomes of cyclophosphamide (CP) therapy in antineutrophil cytoplasmic antibody-associated vasculitis with genotype polymorphisms in prodrug activating cytochrome P450 enzyme genes CYP2C9 and CYP2C19 .Patients & methods: One hundred and ninety six patients with antineutrophil cytoplasmic antibody-associated vasculitis treated with CP, either as intravenous pulse or as daily oral medication, were included. Genotypes of CYP2C9 and CYP2C19 were correlated with clinical outcomes (leukopenia, infection, urotoxicity and treatment response).Results: Sixty five (33.2%) patients had variant CYP2C9 and 55 (28.1%) had variant CYP2C19 genotype. In patients bearing variant CYP2C9, leukopenia was documented significantly more frequent than in carriers of wild-type CYP2C9 (55.4 vs 37.4%; odds ratio: 2.08; 95% CI: 1.14–3.80; p = 0.017). The impact of the CYP2C9 genotype was stronger in patients treated with oral CP (69.6 vs 45.6%; odds ratio: 2.73; 95% CI: 1.27–5.89; p = 0.009), but was not present in patients treated with intravenous pulsed CP. We observed less refractory disease courses in patients with variant CYP2C9, not reaching statistical significance.Conclusion : Patients with variant CYP2C9 are at increased risk for cyclophosphamide-induced leukopenia but may have a better chance to respond to treatment.